The effect of D123 wheat as a companion crop on soil enzyme activities, microbial biomass and microbial communities in the rhizosphere of watermelon - Xu, Wei H.; Wang, Zhigang; Wu, Fengzhi (Frontiers in Microbiology, 2015)
The growth of watermelon is often threatened by Fusarium oxysporum f. sp. niveum (Fon) in successively monocultured soil, which results in economic loss. The objective of this study was to investigate the effect of D123 wheat as a companion crop on soil enzyme activities, microbial biomass and microbial communities in the rhizosphere of watermelon and to explore the relationship between the effect and the incidence of wilt caused by Fon. The results showed that the activities of soil polyphenol oxidase, urease and invertase were increased, the microbial biomass nitrogen (MBN) and microbial biomass phosphorus (MBP) were significantly increased, and the ratio of MBC/MBN was decreased (P<0.05). Real-time PCR analysis showed that the Fon population declined significantly in the watermelon/wheat companion system compared with the monoculture system (P<0.05). The analysis of microbial communities showed that the relative abundance of microbial communities was changed in the rhizosphere of watermelon. Compared with the monoculture system, the relative abundances of Alphaproteobacteria, Actinobacteria, Gemmatimonadetes and Sordariomycetes were increased, and the relative abundances of Gammaproteobacteria, Sphingobacteria, Cytophagia, Pezizomycetes, and Eurotiomycetes were decreased in the rhizosphere of watermelon in the watermelon/wheat companion system; importantly, the incidence of Fusarium wilt was also decreased in the watermelon/wheat companion system. In conclusion, this study indicated that D123 wheat as a companion crop increased soil enzyme activities and microbial biomass, decreased the Fon population, and changed the relative abundance of microbial communities in the rhizosphere of watermelon, which may be related to the reduction of Fusarium wilt in the watermelon/wheat companion system.